Snake Envenomation in the Intensive Care Unit of a Tertiary Care Hospital, Dhaka, Bangladesh: A Prospective Cohort Study (Journal of Current and Advance Medical Research, 2022)
Background: Snake bite and the subsequent envenomation is an important health hazard which may lead to fatality in rural areas of Bangladesh.Objective: This study was conducted to evaluate the epidemiology, clinical profile, treatment and outcome for patients with snake bite admitted in the intensive care unit of Dhaka Medical College Hospital, Bangladesh.Methodology: This prospective cohort study was conducted in the Department of Anaesthesia, Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College, Dhaka, Bangladesh from May 2019 to April 2020 for a period one year. The patients of snake bite were treated in the Intensive care unit, Dhaka Medical College Hospital, Dhaka, Bangladesh. A questionnaire, containing information on bite, physical examination and identification of snake was used.Results: A total number of 23 patients of snake bite were treated in the Intensive care unit. Among the patients, 16 (69.56%) were bitten by cobra, 2 (8.6%) were suspected to be bitten by krait and 5(21.7%) cases had Russel viper bite. Tight tourniquet was used in 15(65.21%) cases. Among the patients 18(78.26%) patients were observed with the features of neurotoxicity with or without local envenoming. Among all patients, one patient required two doses of ASV, another patient needed 3 doses; but the other patients were found to be improved after getting a single dose of ASV. However, 15 patients needed ventilator support. The mean duration of ventilator support was 4.8 days. The mortality was 30.43% (7 patients). Out of these 7 patients, 4 patients died due to acute renal failure with DIC.Conclusion: Neuroparalytic Cobra envenomation is accounted for the highest incidence of venomous bites in the present study.Journal of Current and Advance Medical Research, January 2022;9(1):48-55